Aplicação de inulinases de leveduras isoladas do semi-árido para a produção de concentrados de frutose - Nascimento, Diego Sampaio (2010)
Inulinases target the β-2 linkage of inulin, a poliyfructan consisting of linear β-2,1 linked fructose, and hydrolyzes it into fructose. The use of inulinases provides an alternative way to obtain fructose syrup through the hydrolysis of inulin. The objective of this work was to study the production, characterization and application of an inulinase from Pseudozima sp CCMB 300, Kluyveromyces marxianus (CCMB 322) and fungal endophytes (CCMB 328) isolated from Brazilian semi-arid region. The enzyme was characterized on the kinetic and stability nature and the results suggest that the isolated inulinase has potential for inulin hydrolysis reported rates of up to 100% conversion of inulin to fructose.